A Diabetes Education Model in Primary Care: Provider and Staff Perspectives. Issue 5 (October 2019) - Siminerio, Linda; Hamm, Megan; Kanter, Justin; Cameron, Flor de Abril; Krall, Jodi
Purpose: The purpose of this qualitative study was to explore the effectiveness of Glucose to Goal (G2G), a diabetes self-management education and support (DSMES) model for primary care (PC). Methods: PC providers and staff were recruited from 5 PC practices participating in the 18-month intervention to participate in focus groups and interviews, which were used to gain insights about their perspectives on DSMES and how G2G was implemented across the intervention. Data were collected by qualitative researchers at baseline, midpoint, and study completion. Results: At baseline, PC participants held a favorable view of DSMES and welcomed having a diabetes educator (DE) in their practice. Most participants suggested DEs would be helpful in meeting patients' nutrition needs but should give therapeutic advice only with a doctor's oversight. Participants anticipated that having a DE onsite would mitigate transportation, scheduling, communication, and cost barriers. Participant viewpoints about G2G remained unchanged from midpoint to study end, while barriers regarding location and transportation were perceived as being reduced by having a DE in the practice. Despite referral rates remaining low in some practices, many concerns stated at earlier timepoints appeared to have been attenuated by G2G components (eg, bringing the DE onsite, preidentifying patients, and DE ability to communicate and make diabetes management recommendations). Conclusions: This study demonstrates that G2G, providing DSMES in PC, appeared to be a welcome service where acceptance of and enthusiasm for the model grew over the course of the intervention.